2017
DOI: 10.5194/acp-17-11423-2017
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory responses to secondary organic aerosols (SOA) generated from biogenic and anthropogenic precursors

Abstract: Abstract. Cardiopulmonary health implications resulting from exposure to secondary organic aerosols (SOA), which comprise a significant fraction of ambient particulate matter (PM), have received increasing interest in recent years. In this study, alveolar macrophages were exposed to SOA generated from the photooxidation of biogenic and anthropogenic precursors (isoprene, α-pinene, β-caryophyllene, pentadecane, m-xylene, and naphthalene) under different formation conditions (RO 2 + HO 2 vs. RO 2 + NO dominant, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
128
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(142 citation statements)
references
References 111 publications
(156 reference statements)
13
128
1
Order By: Relevance
“…Also cellular tests with an ROS probe have been developed to measure ROS induced by aerosols in a biological system (Landreman et al, 2008;Zhang et al, 2016;Tuet et al, 2017). The DCFH (2 ,7 -dichlorofluorescin) assay has been shown to be sensitive to a broad range of organic peroxides, alkyl peroxide radicals, and hypochlorite, but not to components that are known to induce redox cycling (i.e., metal ions and quinones; Venkatachari and Hopke, 2008;Wang et al, 2011b;King and Weber, 2013;G. W. Fuller et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also cellular tests with an ROS probe have been developed to measure ROS induced by aerosols in a biological system (Landreman et al, 2008;Zhang et al, 2016;Tuet et al, 2017). The DCFH (2 ,7 -dichlorofluorescin) assay has been shown to be sensitive to a broad range of organic peroxides, alkyl peroxide radicals, and hypochlorite, but not to components that are known to induce redox cycling (i.e., metal ions and quinones; Venkatachari and Hopke, 2008;Wang et al, 2011b;King and Weber, 2013;G. W. Fuller et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…W. Fuller et al, 2014;. The DCFH assay has fast response rates and a linear response to varying ROS concentrations, for which reason it was applied as a suitable measure for the PB-ROS concentration (Zhou et al, 1997;Venkatachari and Hopke, 2008;Weber, 2013, Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the SOA reactions concern the heterogenic aerosol chemistry section that is they are beyond the scope of our study. For more details about the SOA paths, please see the studies in Reference [65][66][67][68]. Therefore, we distinguish the quasi-heterogeneous gas chemistry and the heterogeneous gas chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Various experiments have also shown that pure SOA does induce adverse effects upon exposure of airway epithelial cells (Arashiro et al, 2016(Arashiro et al, , 2018Gaschen et al, 2010;Lin et al, 2016;Chowdury et al, 2018;Jiang et al, 2016). Similarly, cellular based ROS assays show a strong connection with pure SOA or its fraction in PM (Tuet et al, 2016;Tuet et al, 2017a;Tuet et al, 2017b;Saffari et al, 2014). Further, Lakey et al (2016) developed a model to simulate the response of air pollutants including PM on the production rates and concentrations of ROS in the epithelial lining fluid of the human respiratory tract.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%